Analysis of the Budget for the Sales Target of Aqua and Le Mineral Products - Irianti, Reni; Yana, Rubby (Maksi, 2024)
The structure of the bottled drinking water (AMDK) industry in Indonesia has undergone significant development over the past few decades. Amidst intense competition, Aqua and Le Minerale have emerged as two major brands dominating the AMDK market. This article aims to analyze the sales target budgets of these two brands through a competitive analysis approach. The research employs a quantitative descriptive method, utilizing sales budget reports from both brands as primary data samples. The analysis evaluates market positioning, marketing strategies, variables influencing consumer preferences, and the impact of pricing policies implemented by each company. The findings reveal that Le Minerale has successfully built a strong brand image through superior product quality and innovative marketing efforts, despite Aqua maintaining its position as the market leader. This study provides strategic insights for AMDK industry players to enhance their competitiveness and performance in an increasingly competitive market landscape.